Novel Viroid‐Like RNAs Naturally Infect a Filamentous Fungus (Adv. Sci. 3/2023). Issue 3 (25th January 2023) - Dong, Kaili; Xu, Chuan; Kotta‐Loizou, Ioly; Jiang, Jingjing; Lv, Ruiying; Kong, Linghong; Li, Shifang; Hong, Ni; Wang, Guoping; Coutts, Robert H. A.; Xu, Wenxing
Abstract : Viroid‐Like RNAs In article number 2204308, Wenxing Xu, Kaili Dong, and co‐workers characterize a novel class of viroid‐like RNAs naturally infecting a filamentous fungus Botryosphaeria dothidea isolated from apple and termed as mycoviroids. These mycoviroids replicate autonomously in the nucleus via a rolling‐circle mechanism following a symmetric pathway, can apparently modulate specific biological traits of the host fungus, and represent a new class of acellular entities endowed with regulatory functions, and novel epigenomic carriers of biological information. This is the first report of infectious viroid‐like RNAs (or exogenous small circular RNAs) in a life kingdom (fungi) other than plants.